A technique of stretched meshes in the modelling of complex 3D structures in Finite Elements Analysis (FEA) applications - Smykla, A. (Computer Assisted Methods in Engineering and Science, 2006)
The paper presents the computational approach to the process of creation of complex three-dimensional finite elements models. The data are automatically received by the measuring unit and sent directly to the computer. The process of numerical treatment of measuring points' coordinates is shown. As an example of above mentioned method, the construction of human femoral head model is demonstrated. Finally the geometrical model of the object, which can be used by PATRAN system is obtain. Paper presents results of numerical calculations and compares it with a photoelastic experiment.